Boil Myiasis in Young Adult with Psoriasis, Description of an Entity Associated with Underdevelopment in the Americas (Revista de Medicina Clinica, 2023)
Clinical Snapshot on "Furunculous Myiasis in Young Adults with Psoriasis, Description of an Entity Associated with Underdevelopment in the Americas" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.